An example of the efforts of the Committee of Union and Progress to enlighten the public: Kastamonu education club. - ÇİYDEM, Erol (Turkish History Education Journal (TUHED), 2022)
The present study aims to reveal the aims and activities of the Education (Maarif) Club, which was established by the Committee of Union and Progress in Kastamonu shortly after the declaration of the Second Constitutional Monarchy (1908) in the Ottoman Empire. The re-declaration of the Constitutional Monarchy after a long period of oppression led to the emergence of a liberal atmosphere in the Ottoman country. In this process, the bans on the establishment of organizations such as societies and associations came to an end. In this process, the attempts of the Committee of Union and Progress to increase its influence in the country stand out. It is also known that the members of the society attached great importance to educational activities in line with the enlightenment of the people. By positioning themselves as guides in front of the public, the members of the society used education as a tool to enlighten the public. In this direction, various clubs were established by the Committee of Union and Progress in the center and provinces. One of these was the Education Club established in Kastamonu. The purpose and activities of the Education Club provide important information about the education policy pursued in the early years of the Second Constitutional Monarchy, the ideology of the period, etc. From this point of view, this study is important in terms of revealing what kind of a mission the Committee of Union and Progress attributed to education, especially in the early years of the Second Constitutional Monarchy. While examining a historical period, such local history studies will also fulfill many possible information gaps in historical narratives created only through a particular center, event, or phenomenon. A historical research method was used in the study. The data in the study were obtained by scanning the Kastamonu Provincial Newspaper. The document analysis method was used to analyze the data.